Neoliberal Discourse in Digital Sociopreneurship: A Foucauldian Analysis - Juan Pinantun Pakpahan; Bambang Dwi Prasetyo; Fitri Hariana Oktaviani (ETTISAL : Journal of Communication, 2026)
This study examines how neoliberal ideology is reproduced within digital sociopreneurial communication by analyzing Garda Pangan, a foodbank sociopreneurial organization operating in Surabaya and Malang, Indonesia. The research addresses a core problem in contemporary humanitarian campaigns, namely the tendency to frame structural issues such as food waste and food insecurity as matters of individual moral responsibility. Using Foucauldian Discourse Analysis within the Critical–Cultural Tradition, this study investigates how visual and textual narratives on Instagram construct moral subjectivities, responsibilize audiences, and normalize neoliberal rationalities. The findings identify four dominant discursive formations: food waste as moral failure, charity as redemption, volunteering as lifestyle identity, and institutional discipline of virtue. These formations reveal how digital campaigns aestheticize empathy, individualize responsibility, and transform humanitarian action into performative moral practice. The analysis of organizational guidelines further demonstrates how institutional discourse reinforces moral governance and self-regulation. The study concludes that Garda Pangan’s communication reconfigures collective ethics into individualized virtue, thereby depoliticizing the structural dimensions of food insecurity. This research contributes to critical communication scholarship by showing how power operates through moral discourse in digital sociopreneurship.